Antioxidant Activity and Total Phenolic and Flavonoid Content of Various Solvent Extracts from In Vivo and In Vitro Grown Trifolium pratense L. (Red Clover) - Esmaeili, A.K.; Taha, R.M.; Mohajer, S.; Banisalam, B. (Hindawi Publishing Corporation, 2015)
In the present study the extracts of in vivo and in vitro grown plants as well as callus tissue of red clover were tested for their antioxidant activities, using different extraction solvent and different antioxidant assays. The total flavonoid and phenolic contents as well as extraction yield of the extracts were also investigated to determine their correlation with the antioxidant activity of the extracts. Among all the tested extracts the highest amounts of total phenolic and total flavonoids content were found in methanol extract of in vivo grown plants. The antioxidant activity of tested samples followed the order in vivo plant extract > callus extract > in vitro extract. The highest reducing power, 2,2-azino-bis-(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical scavenging, and chelating power were found in methanol extracts of in vivo grown red clover, while the chloroform fraction of in vivo grown plants showed the highest 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, superoxide anion radical scavenging and hydrogen peroxide scavenging compared to the other tested extracts. A significant correlation was found between the antioxidant activity of extracts and their total phenolic and total flavonoid content. According to the findings, the extract of in vitro culture of red clover especially the callus tissue possesses a comparable antioxidant activity to the in vivo cultured plants’ extract.